2016
DOI: 10.1002/cplu.201600303
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Catalyst for Light‐Driven Green Molecular Transformations

Abstract: This Minireview is focused on the development of hybrid catalysts composed of photosensitizers and a metal complex, especially vitamin B12 derivatives. The semiconductor–metal complex composites are effective photocatalysts for molecular transformations due to the synergistic effect between the two components. The design of a B12 complex for the hybridization with TiO2 was simple and straightforward—cobyrinic acid, having seven carboxylic groups derived from naturally occurring B12 is stably immobilized on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 122 publications
0
20
0
Order By: Relevance
“…Cobalt−carbon complexes are among the most studied organometallic bonds . These complexes act as important synthetic intermediates that can be cleaved homolytically by photolysis, electrolysis, or thermolysis to generate Co(II) and carbon‐centered radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt−carbon complexes are among the most studied organometallic bonds . These complexes act as important synthetic intermediates that can be cleaved homolytically by photolysis, electrolysis, or thermolysis to generate Co(II) and carbon‐centered radicals.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that the treatment of ah ydrophobic vitaminB 12 derivative, heptamethyl dicyanocobyrinate ((CN) 2 Cby(OMe) 7 ), with 65 %n itric acid gives a nitrated derivative of cobalamin in 78 %y ield. [35] Unfortunately,a pplyingt he same conditions for the nitration of 1 results in am ixture of products and only 19 %y ield of the desired (CN)Cbl(10-NO 2 ) (2)( Ta ble 1, entry 1).…”
Section: Synthesismentioning
confidence: 99%
“…Vitamin B 12 (1;F igure 1) is vital to living organisms because it is involved in aseries of enzymatic reactions (isomerization,dehalogenation, and methyl transfer). [1][2][3] Its catalytic abilities are intrinsically relatedt ot he hexacoordinated cobalt(III)i on chelated by four corrin nitrogen atoms( equatorial ligand), whereas two other ligands( a-, b-) occupy axial positions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations